Kebutuhan Guru Bahasa Arab di Sekolah Muhammadiyah Se Kota Yogyakarta - Ana Taqwa Wati; Dipim Pratimi; Novela Gibyana Widayat (DIDAKTIKA, 2025)
This study aims to determine the percentage of the educational background of Arabic language teachers in Muhammadiyah schools in Yogyakarta city by calculating the percentage of graduates of Arabic language education and non-Arabic language education. This research uses descriptive quantitative research with documentation data collection techniques in the form of Arabic language teacher data in Yogyakarta and calculated using the percentage formula. The results showed 186 Arabic teachers in Yogyakarta city from every level of education. Most of these teachers do not have a background in Arabic education. The data for each school level include 74 teachers in high school with a percentage of PBA graduates of just 7%, 50 teachers in junior high school with a percentage of 4%, and in elementary school there are 62 teachers with a percentage of only 10% and the overall percentage value of teachers with Arabic language education backgrounds only amounts to 7% with Arabic language education backgrounds. So that from the results of the percentage calculation, it is known that there are still many Muhammadiyah schools in the city of Yogyakarta that do not have teachers with Arabic language education backgrounds so Muhammadiyah schools in the city of Yogyakarta still need Arabic language teachers who have PBA graduates.